Rotting fungi of pomegranate fruit from southern Italy. Symptoms, fungal characterization, and pathogenicity - Mincuzzi A.; Ippolito A.; Sanzani S.M. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
Pomegranate (Punica granatum L.) is an increasingly important crop in Apulia region (southern Italy), where most of the Italian production occurs. The main yield problem is related to postharvest losses caused by fungi. The present research was conducted using fruit of various cultivars (Acco, Mollar de Elche, Wonderful, and Wonderful One), from local markets, orchards, and packinghouses. Four new postharvest fungal pathogens of pomegranate fruit were identified: Pilidiella granati, Cytospora punicae, Talaromyces albobiverticillius, and Colletotrichum acutatum s.s.. The last fungus caused antrachnose, whereas the three others rots with characteristic symptoms. The macro- and micro-morphological traits and the molecular characterization of the pathogens allowed the species identification. Koch’s postulates supported the pathogenicity of these fungi. They might represent a serious threat for this promising crop.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)